Point of care gastric ultrasound to predict aspiration in patients undergoing urgent endotracheal intubation in the emergency medicine department - Reshma Asokan; Bharat Bhushan Bhardwaj; Naman Agrawal; Udit Chauhan; Aadya Pillai; Takshak Shankar; D. J. Lalneiruol; Himanshi Baid; Hannah Chawang; Sanket Mukeshkumar Patel (BMC Emergency Medicine, 2023)
Abstract Background One significant cause of morbidity and mortality in patients undergoing endotracheal intubation is the aspiration of gastric contents. Its prevalence is more in the emergency than in elective settings. Point-of-care gastric ultrasound (GUS) is a non-invasive bedside ultrasonogram that provides both qualitative and quantitative information about the stomach contents. The diagnostic accuracy of GUS in terms of gastric parameters (measured antral diameters, antral cross-sectional area, and calculated gastric volume) to predict aspiration is yet unknown. We aim to determine this in the patients undergoing urgent emergency intubation (UEI) in the emergency department. Methodology A prospective observational study was conducted at the emergency department of a tertiary healthcare center in India. Patients requiring UEI were identified and a bedside gastric ultrasound was done in the right lateral decubitus position using low frequency curved array probe. The qualitative data and the antral diameters (anteroposterior and craniocaudal) were assessed. The patient's clinical parameters and history regarding the last meal were noted. The cross-sectional area of gastric antrum was calculated using CSA = (AP × CC) π/4. The gastric volume is estimated using Perla's formula: GV = 27.0 + 14.6(RLD CSA) –1.28(age). Results A hundred patients requiring urgent endotracheal intubation were enrolled in the study. Visible aspiration was more in participants with a distended gastric status (χ2 = 16.880, p =  < 0.001). The median gastric volume in the patients who aspirated was 146.37 mL, and it ranged from 111.59 mL-201.01 mL. Using ROC analysis, a cut-off of CC diameter ≥ 2.35 cm (sensitivity 88%, specificity 91%) and AP diameter ≥ 5.15 cm (sensitivity 88%, specificity 87%) predicts aspiration. A calculated USG CSA cut-off ≥ 9.27cm2 (sensitivity 100%, specificity 87%) and an USG gastric volume ≥ 111.594 mL (sensitivity 100%, a specificity 92%) predicts aspiration. Conclusion Point-of-care gastric ultrasound is an useful non-invasive bedside tool for risk stratification for aspiration in busy emergency rooms. We present threshold gastric antral parameters that can be used to predict aspiration along with its diagnostic accuracy. This can help the treating ED physician take adequate precautions, decide on intubation techniques and treatment modifications to aid in better patient management.